2014
DOI: 10.3892/ijo.2014.2385
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine effects of stem cells in wound healing and cancer progression

Abstract: Stem cells play an important role in tissue repair and cancer development. The capacity to self-renew and to differentiate to specialized cells allows tissue-specific stem cells to rebuild damaged tissue and cancer stem cells to initiate and promote cancer. Mesenchymal stem cells, attracted to wounds and cancer, facilitate wound healing and support cancer progression primarily by secreting bioactive factors. There is now growing evidence that, like mesenchymal stem cells, also tissue-specific and cancer stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 120 publications
1
45
0
Order By: Relevance
“…In the case of wound healing, uMSCs attenuate tissue damage, inhibit fibrotic remodeling and apoptosis, promote angiogenesis, stimulate endogenous stem cell recruitment and proliferation, and reduce immune responses. However, the prevalent hypothesis has shown that, when used in cell-based therapy, uMSCs mainly provide benefits for wound healing via paracrine mechanisms [18,32]. Despite the early accumulation of systemically administered uMSCs at the site of injury, few uMSCs become permanently engrafted within the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of wound healing, uMSCs attenuate tissue damage, inhibit fibrotic remodeling and apoptosis, promote angiogenesis, stimulate endogenous stem cell recruitment and proliferation, and reduce immune responses. However, the prevalent hypothesis has shown that, when used in cell-based therapy, uMSCs mainly provide benefits for wound healing via paracrine mechanisms [18,32]. Despite the early accumulation of systemically administered uMSCs at the site of injury, few uMSCs become permanently engrafted within the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, MVs may provide a novel means for the development of prospective strategies of cell-free regenerative therapies ultimately aiming to tackle otherwise intractable pathologies, improve age-related health span and mitigate the effects of degenerative diseases by tissue regeneration [36]. …”
Section: Mode Of Actionmentioning
confidence: 99%
“…The use of epithelial cells in tissue restoration and wound healing has attracted considerable interest. As such, the number of studies that seek to employ epithelial cells with high therapeutic potential to create novel therapies that can target and ultimately restore tissue integrity has been increasing (2)(3)(4). Chronic cutaneous wounds are one of the most unfavorable pathophysiological processes in dermatologic surgery; however, they may be treated using cell-based therapy development (5).…”
Section: Introductionmentioning
confidence: 99%